Acute hypercarbia increases the lower limit of cerebral blood flow autoregulation in a porcine model. (3rd March 2016) - Nusbaum, Derek M.; Brady, Kenneth M.; Kibler, Kathleen K.; Blaine Easley, Ronald
Abstract : Objectives: In the present study, our objective was to determine if hypercarbia would alter cerebral blood flow (CBF) autoregulation and reduce the ability of cerebrovascular reactivity monitoring to identify the lower limit of cerebrovascular autoregulation (LLA). Methods: Anaesthetised juvenile pigs were assigned between two groups: normocarbia (control group, n  = 10) or hypercarbia [high carbon dioxide (CO2 ) group, n  = 8]. Normocarbia subjects were maintained with an arterial CO2 of 40 Torr, while the hypercarbia subjects had an increase of inspired CO2 to achieve an arterial pCO2 of >80 Torr. Gradual hypotension was induced by continuous haemorrhage from a catheter in the femoral vein, and the LLA was determined by monitoring cortical laser Doppler flux (LDF). Vascular reactivity monitoring was performed using the pressure reactivity index (PRx) and haemoglobin volume index (HVx). Results: There were no sustained differences in ICP between groups. Autoregulation was present in both groups, despite elevation in pCO2 .The control group had an average LLA of 45 mmHg (95% CI: 43–47 mmHg) and the high CO2 group had a LLA of 75 mmHg (95% CI: 73–77 mmHg). The detected LLA for each subject correlated with the level of pCO2 (spearman R  = 0.8243, P  < 0.0001). Both the PRx and HVx accurately detected the LLA despite the presence of hypercarbia. Discussion: Hypercarbia without acidosis increases the observed LLA independent of alterations in ICP. Elevations in CO2 can impair cerebrovascular autoregulation, but if there is a sufficient increase in blood pressure above the CO2 altered LLA, then autoregulation persists.